Ethanolic periwinkle leaf extract reduces telomerase expression in T47D cancer cells - Endang Purwaningsih; Etty Widayanti; Yulia Suciati (Universa Medicina, 2015)
BACKGROUNDCancer cells have a relatively high telomerase activity and a lower p53 protein expression than normal cells, so that cancer cells have the ability to continue to proliferate and do not undergo apoptosis. One of the cancer treatments is chemotherapy using bioactive ingredients from synthesis or isolation of natural materials. One of the plants that have potential as anticancer agent is periwinkle (Catharanthus roseus L). The research objective was to evaluate the effect of ethanolic periwinkle leaf extract against p53 protein and telomerase expression in T47D cancer cells.  METHODSAn experimental study with controls was conducted involving T47D breast cancer cells. They were divided into 3 groups (control, ½ dose of IC50/26.849 µg/mL, and one dose of IC50/53.699 µg/mL) at a cell density of 1 x 104 cells/well. Expression of p53 and telomerase was measured by the immunohistochemistry method. Data were analyzed using one-way ANOVA followed by a multiple comparison test.RESULTSPeriwinkle leaf extract significantly increased p53 protein expression (p<0.05) at both treatment doses, ½ IC50 and IC50, compared to the control group and it highly significantly reduced telomerase expression (p<0.01), in comparison with the control group at both treatment doses. CONCLUSIONPeriwinkle leaf extract has potential as an anti-breast cancer agent by increasing p53 protein expression and inhibiting telomerase expression.